Does stock market development promote economic growth? A bounds testing analysis for Bangladesh - Md. Abu Hasan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
The aim of this paper is to investigate the linkage between stock market development and real economic growth in Bangladesh using time series data from 1981 to 2017 employing Autoregressive Distributed Lag (ARDL) bounds testing cointegration procedure and Error Correction Model (ECM). The bounds testing cointegration procedures reveal that stock market size has a significant long run impact on real economic growth in Bangladesh at 5% significance level. The results of the estimated ARDL-ECM models show that a highly significant long-run causality is directing from stock market development to real economic growth. The negative and significant error correction term implies that 81% of the last year’s disequilibrium is corrected this year by changes in real economic growth. Finally, we find that there is no causality running between real economic growth and stock market development in the short run. Stock market performance prompts real economic growth in the long run though the contribution of the stock market in Bangladesh related to money market is still in a transition period. Moreover, bank dominating financial system of Bangladesh is nearly seeming close to the catastrophe bring about by massive nonperforming loans and series of banking scams. Thus, policymakers of Bangladesh should give a boost to the stock market as a complimentary financial system with the banking sector such that economic growth will be contributed better than the results of this study demonstrate.